The Significance of Jesus Christ in Asia - Kochuparambil, V (Journal of Dharma, 1989)
Hans Steffner S.J., The Significance of Jesus Christ in Asia, Anand, India : Gujarath Sahitya Prakash, 1985, pp. Wii + 264. Rs. 35.00.